2018
DOI: 10.7717/peerj.4521
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tides on nearshore environmental DNA

Abstract: We can recover genetic information from organisms of all kinds using environmental sampling. In recent years, sequencing this environmental DNA (eDNA) has become a tractable means of surveying many species using water, air, or soil samples. The technique is beginning to become a core tool for ecologists, environmental scientists, and biologists of many kinds, but the temporal resolution of eDNA sampling is often unclear, limiting the ecological interpretations of the resulting datasets. Here, in a temporally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 36 publications
10
112
1
Order By: Relevance
“…It has previously been suggested that many animal lineages remain unsampled and/or unsequenced, potentially even harboring novel phyla (López-escardó et al, 2018;Nguyen et al, 2019). All sampling methods are subject to methodological limitations, and different sampling methods will capture different subsets of biodiversity (Kelly et al, 2017;Shelton et al, 2016). Like more traditional survey methods, eDNA metabarcoding has a certain level of taxonomic selectivity, which may be the result of primer bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been suggested that many animal lineages remain unsampled and/or unsequenced, potentially even harboring novel phyla (López-escardó et al, 2018;Nguyen et al, 2019). All sampling methods are subject to methodological limitations, and different sampling methods will capture different subsets of biodiversity (Kelly et al, 2017;Shelton et al, 2016). Like more traditional survey methods, eDNA metabarcoding has a certain level of taxonomic selectivity, which may be the result of primer bias.…”
Section: Discussionmentioning
confidence: 99%
“…as of yet, been scarce (Cowart, Murphy, & Cheng, 2017;Djurhuus et al, 2017;Drummond et al, 2015;Günther, Knebelsberger, Neumann, Laakmann, & Martínez Arbizu, 2018;Kelly, Gallego, & Jacobs-Palmer, 2017;Villarino et al, 2018); the majority of these have relied on ribosomal markers, such as 18S Guardiola et al, 2015;Lindeque et al, 2013), 16S , and 12S (Miya et al, 2015), but due to their relatively conserved sequences, it is often impossible to distinguish taxa at the species, genus, or even family level (Tang et al, 2012), which represents a significant limitation to the evaluation of community changes and the biological and/or environmental mechanisms responsible for these changes (Mackas & Beaugrand, 2010).…”
Section: Studies Targeting Marine Eukaryotic Community Diversity Havementioning
confidence: 99%
“…Encouragingly, Harper et al (2018) demonstrated that Triturus cristatus (great crested newt) detection via metabarcoding with no threshold is equivalent to qPCR with a stringent detection threshold. eDNA metabarcoding has also been applied to large-scale investigations of spatial or temporal variation in marine and freshwater communities, with some studies indicating that communities can be distinguished from 100 m to 2 km due to stream discharge or tidal patterns Kelly, Gallego, & Jacobs-Palmer, 2018;Li, Evans, et al, 2018;O'Donnell et al, 2017;Port et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To counteract the inclusion of these organisms into our analysis, we specifically excluded from the analysis any aeDNA from groups with no marine representatives, since our primary interest was to describe the in situ coral reef community. However, lateral mixing may still occur through local currents that transport DNA across reef habitats or sites (Kelly, Gallego, & Jacobs-Palmer, 2018). Moreover, we have presented data from just two sediment cores as a proof of concept; given the different patterns exhibited by PAN1 and PAN3, more replication at the level of cores should increase confidence in the strength of our approach.…”
Section: Limitationsmentioning
confidence: 85%